Effect of Corporate Social Responsibility, Leverage, Firm Age and Size on Firm Value - Serolin, Alvina (SAN Scientific, 2023)
This study aims to analyze the effect of corporate social responsibility, leverage, firm age, and size on firm value and its review from an Islamic point of view. This study was conducted at LQ 45 firms listed on the Indonesia Stock Exchange. This study uses secondary data for the period 2017-2021. The sample in this study was determined using purposive sampling so that 16 firms were obtained with a total of 80 LQ 45 Firm data. The method used is panel data analysis with the Eviews 12 application. The study results show that simultaneously, the ratio of corporate social responsibility, leverage, firm age, and firm size significantly influence the prediction of firm value. Furthermore, the corporate social responsibility ratio partially does not influence firm value. In contrast, the leverage ratio, firm age, and firm size negatively affect firm value. The variables of leverage, firm age, and firm size are very much a consideration for investors to choose a good firm or not; therefore, these variables significantly affect firm value.